2022
DOI: 10.1007/s00221-022-06518-0
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and perceived fatigability, not objective fatigability, are prevalent in people with post-COVID-19

Abstract: Persistent symptoms after acute COVID-19 infection, termed post-COVID-19 fatigue, occur in 44–70% of patients. Characterizing fatigue in this population is vital to determine the etiology of post-COVID-19 fatigue symptoms and to assess the effectiveness of potential interventions. The purpose of this study was to assess differences in perceived and objective fatigability between people with post-COVID-19 symptoms ( N = 29, 20 females) and people who had COVID-19 but are not experiencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 72 publications
1
19
0
2
Order By: Relevance
“…190 potential subjects were identified, and thirty-three subjects (17 female) who were previously diagnosed with COVID-19 were eventually enrolled between January 2021 and June 2022. Inclusion criteria were: (1) being between the ages of 18–80, (2) meeting CDC guidelines for discontinuation of home isolation and being at least 6 weeks post-quarantine; (3) having the ability to read, write, speak, and understand English, as well as comprehension of the protocol; (4) confirming the COVID-19 diagnosis via medical record; and (5) experiencing or not experiencing PCS symptoms (depending on group assignment), according to the Chalder Fatigue Scale CFQ-11 (PCS fatigue ≥5 [ 6 , 22 ]; completed via email or phone). Exclusion criteria were: (1) history of traumatic brain injury or hydrocephalus; (2) pregnancy; (3) the presence of any medical condition that may exacerbate any post-COVID-19 symptoms (e.g., major depressive disorder, anxiety disorder); and (4) hospitalization due to COVID-19 infection.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…190 potential subjects were identified, and thirty-three subjects (17 female) who were previously diagnosed with COVID-19 were eventually enrolled between January 2021 and June 2022. Inclusion criteria were: (1) being between the ages of 18–80, (2) meeting CDC guidelines for discontinuation of home isolation and being at least 6 weeks post-quarantine; (3) having the ability to read, write, speak, and understand English, as well as comprehension of the protocol; (4) confirming the COVID-19 diagnosis via medical record; and (5) experiencing or not experiencing PCS symptoms (depending on group assignment), according to the Chalder Fatigue Scale CFQ-11 (PCS fatigue ≥5 [ 6 , 22 ]; completed via email or phone). Exclusion criteria were: (1) history of traumatic brain injury or hydrocephalus; (2) pregnancy; (3) the presence of any medical condition that may exacerbate any post-COVID-19 symptoms (e.g., major depressive disorder, anxiety disorder); and (4) hospitalization due to COVID-19 infection.…”
Section: Methodsmentioning
confidence: 99%
“…The Fatigue Severity Scale (FSS) consists of nine statements to evaluate perceived fatigue [ 6 ], each rated on a 7-point scale with higher numbers representing higher agreement with the statement. The scores of each question are averaged to give an overall score between 1 and 7, with a score ≥4 indicating a clinically significant level of fatigue [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many exercise protocols have been used in the literature, for instance using maximal incremental test [e.g., ( 22 )], the “classic” fatiguing protocols involve repetitions of sustained MVC [e.g., ( 23 )] or repetitions of MVCs either in isometric [e.g., ( 24 )] or isokinetic mode [e.g., ( 25 )]. Then a fatigue index that consists in normalizing the last contractions to the initial ones is calculated.…”
Section: Measuring Objective Fatigability Resistance: How?mentioning
confidence: 99%
“…In this line, Matta et al (2022) suggested that physical symptoms continuing 10-12 months after the first wave of the COVID-19 pandemic may be related more with the idea in having experienced COVID-19 rather than with an actual positive test. Importantly, previous work showed that perceived fatigability and fatigue are more prevalent than objective fatigability in post COVID-19 patients (Fietsam et al, 2022). They compared fatigue, perceived fatigue, and objective fatigability in these patients both with and without reported persistent fatigue symptoms.…”
mentioning
confidence: 97%